2020
DOI: 10.4314/jae.v24i2.1
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Improved Maize Production Technologies in Punjab Province, Pakistan

Abstract: The study assessed farmers’ awareness and adoption of maize production technologies in Punjab Province, Pakistan. A simple random sampling technique was used to collect data from 120 farmers in the study area through personal interview using a structured interview schedule. The study found that 48.3% of the respondents had obtained information about agricultural practices from extension agents and that 65% of the respondents regularly visited the agricultural extension department. Furthermore, 62.5% of the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…A positive relationship between education and FTC based training may show that more educated people are more adopter of technology than others and able to understand and apply different sort of training provided in FTC which helps them to attend the training regularly. This is consistent with the study conducted by (Muhammad, 2020;Danso-Abbeam et al, 2017;Kadafur et al, 2017;Mmbando & Baiyegunhi, 2016;Salifu & Salifu, 2015). Moreover, it was found that a one contact made with development agent increases the probability of participation in FTC based training by 1.5 units keeping the other factors constant.…”
Section: Determinants Of Farmers' Participation In Ftc Based Trainingsupporting
confidence: 92%
“…A positive relationship between education and FTC based training may show that more educated people are more adopter of technology than others and able to understand and apply different sort of training provided in FTC which helps them to attend the training regularly. This is consistent with the study conducted by (Muhammad, 2020;Danso-Abbeam et al, 2017;Kadafur et al, 2017;Mmbando & Baiyegunhi, 2016;Salifu & Salifu, 2015). Moreover, it was found that a one contact made with development agent increases the probability of participation in FTC based training by 1.5 units keeping the other factors constant.…”
Section: Determinants Of Farmers' Participation In Ftc Based Trainingsupporting
confidence: 92%
“…In Cherangani, the minimum was 0.3 acres and the maximum was 70 acres while Wundanyi farmers reported a minimum of 0.3 acres and a maximum of 8 acres. Ruzzante and Bilton [22], Mudassir et al [23] and Darkwah et al [21] observed that farmers with larger farms were more likely to adopt conservation practices. However, our results further suggest that, depending on the farm size, farmers preferred different types of conservation practices, as discussed later.…”
Section: Socio-economic Profiles Of the Catchment Communitiesmentioning
confidence: 99%
“…In fact, most study that focused on the same issues found some of these barriers. Muddassir et al (2020) Highlighted the importance of building a solid reputation for the extension services among any rural community members, and that can be accomplished by developing effective programs and building trusted relationship with the local community. The trust between local people and extension office has emerged in a set of studies such as Awad (1993).…”
Section: Non-agricultural Activitiesmentioning
confidence: 99%